Exploring Leadership in Kedaireka Ecosystem Programs as a Matchmaking Platform Between Universities and Industries - Akbari, Taufan Teguh; Bustami, Mohammad Reevany (Journal of Leadership in Organizations, 2024)
Introduction/Main Objectives: This research examines the leadership approach implemented in the Kedaireka platform to unify leaders from various sectors. It studies the factors that motivate leaders across sectors to collaborate and the roles played by these leaders. Background Problems: In Indonesia, the Ministry of Education and Culture has established a collaborative ecosystem named Kedaireka. Kedaireka has developed research-based solutions to address societal problems three years after its founding. However, this study represents the first detailed examination of leadership practices within the platform. Novelty: This research focuses on the leadership practices within the Kedaireka ecosystem. The findings of this study serve as a reference for leading multi-actor ecosystems. Research Methods: This research employs a qualitative approach, utilizing the case study method. The author employed Focus Group Discussions (FGDs) and interviews for data collection. Finding/Results: The author identifies that Kedaireka's foundation is built on shared and agile collaborative leadership within its multi-actor partnerships. The leadership at Kedaireka prioritizes dynamic and transparent communication with stakeholders. A thorough and rigorous monitoring and evaluation system is in place, facilitating the development of impactful research that benefits society. Conclusion: Leadership characterized by humility, innovation, equitable distribution, and a focus on mutual benefits can serve as a model for organizations across Indonesia. These qualities have proven effective within Kedaireka, notably in delivering significant benefits to stakeholders ranging from universities to the industrial sector.